Does Green Purchase Intention Mediate the Effect of Ethical Self Identity on Green Purchase? - Afifah, Imroatul; Kuswati, Rini (Southeast Asian Business Review, 2023)
This research aims to examine the influence of ethical self-identity on green purchasing, mediated by green purchase intention. The study elucidates pro-environmental behavior concerning the purchase of environmentally friendly products that support issues related to the circular economy in the digital era. The research methodology employs a quantitative deductive approach to test hypotheses. A survey research design was used to investigate green purchasing behavior, with a sample size of 205 respondents from the Surakarta city area. Non-probability sampling was utilized employing the purposive sampling method. Instrument tests included assessments for convergent validity, discriminant validity, as well as reliability tests using Cronbach's alpha and composite reliability, confirming valid and reliable results. These instrument tests and hypothesis testing were conducted using Smart PLS 3.2.9 software, generating output for the outer model and inner model. Data analysis involved a two-step algorithm process and bootstrapping. The analysis results indicate that ethical self-identity and green purchase intention significantly influence green product purchasing behavior. It was evidenced that the intention to purchase green products mediates the influence of ethical self-identity on green product purchasing behavior.